RETRACTED: The E-learning for Alzheimer’s Disease - Zhao, Mengyao (EAI Endorsed Transactions on e-Learning, 2023)
RETRACTED: The article has been retracted due to misconduct during the peer review process. The retraction notice can be found here: https://doi.org/10.4108/eetel.12237